The Impact of Gamification-Based Pedagogical Approaches on Academic Performance and Student Engagement in Educational Settings: Jordanian School Teachers’ Perspective - Buthina Ziead Alobidyeen (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: This study investigates the impact of gamification-based pedagogical approaches on academic performance and student engagement from the perspective of Jordanian school teachers. With the increasing integration of technology and innovative teaching methods, understanding the effectiveness of gamification in educational settings becomes crucial. The objective of this research was to explore how gamification strategies influence both academic performance and student engagement, as perceived by Jordanian school teachers.Methodology: Employing a quantitative research approach, a sample of 433 Jordanian school teachers was purposefully selected to participate in the study. The research instrument employed was a closed questionnaire, designed to gather comprehensive insights into teachers’ perceptions of the effects of gamification on academic performance and student engagement. The data collected underwent rigorous analysis using the Smart Partial Least Squares (SmartPLS) technique. This method enabled a robust examination of the relationships between gamification-based pedagogical approaches, academic performance, and student engagement.Findings: The findings emphasize the positive impact of gamification-based pedagogical approaches, shedding light on its potential to transform traditional teaching methods.Implications/Novel Contribution: Policymakers, educators, and curriculum designers can draw upon these findings to make informed decisions aimed at enhancing the quality of education in Jordan and potentially in analogous educational systems globally.